MyPyramid Scramble: Veggie Power! - Linda B. Bobroff (EDIS)
This document is FCS8895, one of a series of 2-page illustrated handouts (puzzle page and key) by Linda B. Bobroff that provide a list of scrambled words forming names of foods in the MyPyramid groups, with numbered letters that form a secret message. Published by the UF Department of Family Youth and Community Sciences, March 2010.